2016
DOI: 10.1115/1.4034240
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Modeling of Ingress in a New 1.5-Stage Turbine Research Facility

Abstract: In gas turbines, hot mainstream flow can be ingested into the wheel-space formed between stator and rotor disks as a result of the circumferential pressure asymmetry in the annulus; this ingress can significantly affect the operating life, performance, and integrity of highly stressed, vulnerable engine components. Rim seals, fitted at the periphery of the disks, are used to minimize ingress and therefore reduce the amount of purge flow required to seal the wheel-space and cool the disks. This paper presents e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…The frequency of Helmholtz resonator can be also determined from equation 3which is a modified version of the equation proposed by Rayleigh [5,6].…”
Section: Fig 1 Feedback Loop Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of Helmholtz resonator can be also determined from equation 3which is a modified version of the equation proposed by Rayleigh [5,6].…”
Section: Fig 1 Feedback Loop Mechanismmentioning
confidence: 99%
“…These examples pertain open flows. Besides, this type of flow occurs in many parts of a gas or steam turbine blade system such as labyrinth seals or rim seals applied between stator and rotor [4,5] and spaces between guiding vanes and turbine casing resulting from its modular construction [12]. Another example is flame stabilizer applied in the ramjet engines.…”
Section: Introductionmentioning
confidence: 99%
“…Hot gas ingestion into the wheel-spaces upstream and downstream of a rotor disk––as shown in Ref. 7 by Patinios et al was investigated. CO2 concentration and other aerodynamic parameters were measured to explore the flow field in wheel-spaces.…”
Section: Introductionmentioning
confidence: 99%
“…This smaller gradient across the lower lip of the double lip seal suggested that it is less sensitive to mainstream-cavity interactions. Recent studies by Balasubramanian et al [17], Patinios et al [18], and Scobie et al [19] have been focused on 1.5-stage axial gas turbines. Balasubramanian et al [17] performed several experiments to measure the ingestion of mainstream air into the front and aft disk cavities in a subscale 1.5-stage axial air turbine.…”
Section: Introductionmentioning
confidence: 99%